Level of physical activity and quality of life associated with health in Paraguay adults - Eliana R. Meza-Miranda; Jazmín Giménez (University of Novi Sad, Faculty of Sport and Physical Education, 2021)
Studies have shown that the performance of scheduled physical activity is positively related to a higher quality of life related to health. The objective of this study was to evaluate the level of physical activity according to the quality of life in the adult population of Paraguay in the period from November to December 2020. A descriptive, analytical cross-sectional design study, which included 211 adults of both sexes. Sociodemographic data such as age, sex and origin were collected, as well as data on physical activity (IPAQ/METS questionnaire) and quality of life (EuroQol-5D questionnaire). The predominant sex was female (89%), 53.5% resided in Gran Asunción and the average age was 34.6±10.6. The level of physical activity was mostly moderate (36.5%). The quality of life index was 0.67±0.15 and the perception of health was 79.12±18.35. Within the dimensions of quality of life, it was observed that 23% had moderate pain or discomfort and that 33% had moderate depression or anxiety. Significant differences were found between the level of physical activity and the quality of life index and the perception of health. The level of physical activity is a determinant of health-related quality of life, the greater the intensity of physical activity, the better the quality and perception of health indices in adults.